KOMUNIKASI EFEKTIF BAGI SEORANG PEMIMPIN - Manalullaili Manalullaili (Wardah, 2012)
Communication is important for leadership. Communication is transmitting meaning and information. Additionally, the leader is as communication champion which communicate does not only convey meaning but also persuade other by using communication skill. To communicate with others, the leader may use effective communication. Communication is the most important part for leaders because effective communication is one of leadership strategy. Effective communication for leaders mean the leaders’ way in communicating res Sometimes, leaders are difficult to transfer information because of communication barriers. The barriers usually come due to misinterpretation. Particularly, leaders should be careful in using nonverbal communication because this is related to body movement, voice and cultural background.ponsibility and effectively.